Pengaruh Konseling Individu dengan Terapi Musik Religi terhadap Kecerdasan Emosional - Apriani, Sri; Kusnawan, Aep; Miharja, Sugandi (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This research was conducted on 11th grade students of MAN 1 Sukabumi, regarding their level of emotional intelligence. Emotional intelligence is one of the important intelligences to be possessed by every student, as the vision and mission of MAN 1 Sukabumi school. The purpose of this study was to determine the effect of individual counseling with religious music therapy on the emotional intelligence of 11th grade students of MAN 1 Sukabumi. The method used in this study was regression with a quantitative approach, using SPSS. From the results of the study, there was an influence of variable X on variable Y. Seen from the hypothesis test, the determination coefficient test obtained a value of 0.240 or 24.0%, and in the regression model obtained a regression coefficient X (Î²) of 0.722.